Treatment of Iatrogenic Subglottic Stenosis by Therapeutic Fibreoptic Bronchoscopy (Journal of Armed Forces Medical College, Bangladesh, 2019)
Endotracheal intubation is a common procedure in intensive care unit. It still qualifies as an invasive procedure. Prolonged endotracheal intubation or intubation with cuffed endotracheal tube in a newborn or young infant is a risk factor for the development of subglottic stenosis. It usually presents with stridor in childhood.  The most likely mechanism of subglottic stenosis is an injury of tracheal mucosa, with secondary scar healing that consequently leads to the development of some degree of subglottic stenosis. Depending on the degree of subglottic stenosis, patients may be asymptomatic for a long time or symptoms can occur within several weeks. The incidence of stenosis is very low if intubation lasts less than a week. Sometimes the patient may develop severe subglottic stenosis after short-term endotracheal intubation. Intubation with cuffed endotracheal tube in newborn results in pressure necrosis and sloughing followed by subglottic stenosis. This article presents a case of a patient (Baby A) who had intubation with cuffed tube which landed to airway problem and stenosis and was managed successfully by taking help from an expert pediatric pulmonologist of a neighbouring country.Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 64-68